PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN MENGKONSUMSI PRODUK KESEHATAN HERBALIFE DI KOTA TERNATE - Machmud, Renawaty; Yusud, Ibnu Sina Hi (Jurnal MS, 2013)
this study aims to determine the â€œinfluence of Product Quality Satisfaction Against Consuming Herbalife Health Products In Ternate.â€ In the 63 respondents, the method of analysis used in The studies are simple line are regression analysis method. Based on statiscal tests showed that the quality of products haved-count equal to 1.053. this value issmaller than the value oft-table (1.053 < 1.999) this result shows that the variable quality of the product (X) does not have asignificant effect oncustomer satisfaction (Y). It can be seenthat the number of R squares quaredor (0.134) ofÂ  0.018. figures R Squaries also known as the coefficient of determination. The magnitude of coefficient of determination 0.018 or 1.8%. The figure of 1.8% means that the quality of Herbalife products may affect customer satisfaction, while the remaining 98.2% (100%-1.8%) affected by other factors such as price and others.